Diagnostic role of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) in abdominal lymphadenopathy of unknown etiology - Wang, Wenli; Han, Chaoqun; Ling, Xin; Guo, Xianwen; Liu, Jun; Lin, Rong; Ding, Zhen (Frontiers in Medicine, 2023)
Background: Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is an established method for the evaluation of abdominal organ lesions. However, there are few studies on EUS-FNA for abdominal lymph node (LN) lesions. The purpose of this study was to evaluate the diagnostic role of EUS-FNA in isolated abdominal lymphadenopathy (LAP). Methods: A retrospective analysis was performed on patients with isolated abdominal LAP who underwent a EUS-FNA examination. The diagnosis was made based on cytology, histology, and immunohistochemical (IHC) studies. The area under curve (AUC) value, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were calculated. Results: A total of 99 patients were included in this study. The final diagnoses were metastatic tumor (n=32), lymphoma (n=32), tuberculosis (n=17), sarcoidosis (n=5), castleman's disease (n=1), and reactive LAP (n=12). The AUC value, sensitivity, specificity, PPV, NPV, and accuracy of EUS-FNA in the diagnosis of malignant LAP were 0.9531, 90.6%, 100%, 100%, 85.4%, and 93.9%, respectively. For the diagnosis of lymphoma, the accuracy of EUS-FNA combined with IHC staining was 94.9%. Retroperitoneal LN enlargement is more commonly associated with lymphoma, while hepatic hilar LN enlargement predominantly suggests benign conditions or metastatic tumors. Malignant lymph nodes are more likely to be regular border, circular/quasi-circular, and fusion. Lymphomas are more likely to present with fusion and heterogeneous echogenicity than metastatic tumors. Conclusion: EUS-FNA is a safe and effective method to diagnose isolated abdominal LAP.